2018
DOI: 10.3324/haematol.2017.186619
|View full text |Cite
|
Sign up to set email alerts
|

The early expansion of anergic NKG2Apos/CD56dim/CD16neg natural killer represents a therapeutic target in haploidentical hematopoietic stem cell transplantation

Abstract: Natural killer cells are the first lymphocyte population to reconstitute early after non-myeloablative and T cell-replete haploidentical hematopoietic stem cell transplantation with post-transplant infusion of cyclophosphamide. The study herein characterizes the transient and predominant expansion starting from the second week following haploidentical hematopoietic stem cell transplantation of a donor-derived unconventional subset of NKp46neg-low/CD56dim/CD16neg natural killer cells expressing remarkably high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
82
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 45 publications
7
82
1
Order By: Relevance
“…Although NK cells reach normal levels and a complete donor chimerism within the first month after allo‐ and haplo‐HSCT, the maturation of NK cells takes longer. Indeed, the distribution of CD56 and CD16 on the surface returns similar to that of healthy donors only after few months from the transplant.…”
Section: Nk Cell Immune‐reconstitution and Nkg2a In Hsctmentioning
confidence: 99%
See 4 more Smart Citations
“…Although NK cells reach normal levels and a complete donor chimerism within the first month after allo‐ and haplo‐HSCT, the maturation of NK cells takes longer. Indeed, the distribution of CD56 and CD16 on the surface returns similar to that of healthy donors only after few months from the transplant.…”
Section: Nk Cell Immune‐reconstitution and Nkg2a In Hsctmentioning
confidence: 99%
“…Instead, the frequency of CD56 br NK cells early after HSCT is remarkably higher than that of CD56 dim , thus further confirming the developmental relationship between these two NK cell subsets. Moreover, we recently reported that the low frequency of CD56 dim NK cells in the first weeks following HSCT is counterbalanced by the expansion of an unconventional NK cell subsets characterized by a CD56 dim /CD16 neg phenotype (uCD56 dim ) . The frequency of this latter NK cell population is very low under homeostatic conditions, although it is endowed with a remarkably high cytotoxicity .…”
Section: Nk Cell Immune‐reconstitution and Nkg2a In Hsctmentioning
confidence: 99%
See 3 more Smart Citations